Challenges in the implementation of community based adaption projects in Eastern and Southern Africa - Osman, Faizal (Department of Construction Economics and Management, 2022)
Community Based Adaptation (CBA) projects in Eastern and Southern Africa have difficulties in achieving long term benefits. There are challenges in the management of the implementation of these projects. This study aimed to determine the facts that contribute to this failure by identifying the main challenges CBA projects face, uncovering how benefits can be better addressed and naming alternatives to the methodology as potential areas of future research. The research used the quantitative method, data collection was done through an online survey directed to professionals with experience in CBA. The analysis of the data showed that long term sustainability, financial factors and stakeholder coordination were the main challenges encountered in CBA projects in the region of study. It was also concluded that focus on stakeholder management, gathering sufficient funds, improving participatory techniques, and improving Project Management (PM) tools or designing a specific PM toolkit for CBA are possible strategies to improve benefits. Ecosystem-based Adaptation (EbA), Information and Communication Technologies Based Adaptation (ICTBA) and Risk Based Adaptation were identified as alternatives to CBA with potential for further study.